Effects of combining diaphragm training with electrical stimulation on pain, function, and balance in athletes with chronic low back pain: a randomized clinical trial - Khadijeh Otadi; Noureddin Nakhostin Ansari; Shahriar Sharify; Zahra Fakhari; Hadi Sarafraz; Amir Aria; Omid Rasouli (BMC, 2021)
Abstract Background It is unknown how diaphragm training combined with electrical stimulation affects pain, function, static stability, and balance in athletes with chronic low back pain (CLBP). This study aimed to explore the effects of combining diaphragm training with electrical stimulation on pain, function, static stability, and dynamic balance in athletes with nonspecific CLBP. Methods The design was a randomized clinical trial. A total of 24 amateur athletes (12 women, 12 men, mean age: 35.2 ± 9.8) with nonspecific CLBP were randomly allocated into two groups. The experimental group (n = 12) received diaphragm training plus Transcutaneous Electrical Nerve Stimulation (TENS), while the control group (n = 12) received TENS alone. Both groups underwent 12 sessions over a four-week period. Static stability, dynamic balance, pain, and function were measured pre- and post-intervention. Results Analysis of variance 2 × 2 revealed greater improvements in pain (p < 0.001), static stability (p < 0.001), and dynamic balance (p < 0.01) in the experimental group compared to the control group. Function was improved in both groups following the interventions (p < 0.001), and there was a trend of a larger improvement in the experimental group than the control group (p = 0.09). Fisher's exact test showed that the experimental group reported ≥50% improvement only in the pain score, not function, compared to the group that received TENS alone (p = 0.005). Conclusions Pain, function, static stability, and dynamic balance were improved in both groups following 12 intervention sessions. However, pain, static stability, and dynamic balance were improved to a greater extent in diaphragm training plus TENS than TENS alone in amateur athletes with CLBP. Therefore, it seems beneficial to add diaphragm training to the rehabilitation program for athletes with nonspecific CLBP. Trial registration The trial was retrospectively registered in the Iranian Registry of Clinical Trials ( www.irct.ir ) on September 10, 2020 as IRCT20090228001719N8 .